Pengaruh Lingkungan Sekolah, Perhatian Orang Tua dan Kebiasaan Belajar Siswa SMA Negeri 1 Ketapang - Umroh, Umroh; El_Yunusi, Muhammad Yusron Mulana; Darmawan, Didit (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
In the current era of globalization, students are faced with demands to consider factors influencing their academic achievements. This research aims to uncover the role of an effective school environment, parental attention, and study habits in enhancing students' educational quality. Quantitative methods were employed in this study. This approach was chosen to provide a more measurable understanding of the roles of the school environment, parental involvement, and study habits on students' academic outcomes. Involving 207 students as research samples, sampling was conducted randomly. Data collection was carried out through distributing questionnaires covering school environment variables, parental involvement, and study habits. Data analysis was conducted through validity testing, reliability testing, classical assumption testing, and multiple linear regression. The use of multiple linear regression as a data analysis tool enabled researchers to understand the extent to which certain variables, such as the school environment, parental involvement, and study habits, contribute to variations in students' academic outcomes. Findings indicate that the school environment plays a significant role in determining students' academic achievements. Emotional involvement and parental support also contribute to students' academic performance. Furthermore, consistent and effective study habits have proven to be significant factors in developing students' academic achievements. With a supportive school environment for learning and positive contributions from parents, as well as effective study habits, it is expected that students' academic outcomes will improve.